2022
DOI: 10.3389/fnins.2021.736524
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Stability of Functional Networks: A Measure to Assess the Robustness of Graph-Theoretical Metrics to Spatial Errors Related to Brain Parcellation

Abstract: There is growing interest in studying human brain connectivity and in modelling the brain functional structure as a network. Brain network creation requires parcellation of the cerebral cortex to define nodes. Parcellation might be affected by possible errors due to inter- and intra-subject variability as a consequence of brain structural and physiological characteristics and shape variations related to ageing and diseases, acquisition noise, and misregistration. These errors could induce a knock-on effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Graph theory is applied to fMRI to study the architecture and complexity of functional networks [ 9 , 10 ] with relevant clinical applications [ 11 ]. Newly diagnosed gliomas demonstrated globally altered functional connectomic profiles in previous studies [ 12 ], while distributed changes of the functional connectome have been shown in glioblastoma patients after surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Graph theory is applied to fMRI to study the architecture and complexity of functional networks [ 9 , 10 ] with relevant clinical applications [ 11 ]. Newly diagnosed gliomas demonstrated globally altered functional connectomic profiles in previous studies [ 12 ], while distributed changes of the functional connectome have been shown in glioblastoma patients after surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the METEOR app can be used to explore the variability of the options, and the one that was commonly used, in the preprocessing steps and facilitate a more informed discussion. The above examples of the variability of the Options in the software and parcellation have also been discussed previously by Bowring et al (2019) and Franco (2022). As an illustration, we examined the variability of Options in the size of the kernel in spatial smoothing, which was also addressed in a previous study by Alahmadi (2021).…”
Section: Meteor App As a Decision Support Toolmentioning
confidence: 73%
“…As with the structural neuroimaging techniques, the variety of approaches and methods used in functional network research requires appropriate approaches to verify and increase the reproducibility of results ( Niu et al, 2013 ; Zuo et al, 2014 ; Zuo and Xing, 2014 ; Geng et al, 2017 ; Adamovich et al, 2022 ; Bottino et al, 2022 ; Kato et al, 2022 ; Rolle et al, 2022 ; Wang et al, 2022 ; Helwegen et al, 2023 ). This applies even more to the fusion of structural and functional imaging techniques ( Luat and Chugani, 2008 ; Aiello et al, 2016 ; Babaeeghazvini et al, 2021 ; Wu et al, 2021 ) as well as to the combined use of different functional imaging techniques (e.g., EEG-fNIRS or EEG-fMRI) that is often pursued to balance the disadvantages of one method with the advantages of another method ( Machado et al, 2011 ; Nguyen et al, 2012 ; Centeno and Carmichael, 2014 ; Obrig, 2014 ; Pittau and Vulliemoz, 2015 ; Tousseyn et al, 2015 ; Abreu et al, 2018 ; Sanz-Garcia et al, 2018 ; Rizkallah et al, 2020 ; Anderson et al, 2021 ; Bernabei et al, 2021 ; Uchitel et al, 2021 ; Ikemoto et al, 2022 ; Li et al, 2022 ; Mulert and Lemieux, 2023 ).…”
Section: Techniques To Assess and Characterize A Time-evolving Brain ...mentioning
confidence: 99%